IMPROVING THE QUALITY OF MULTISECTORAL EDUCATION THROUGH INTER- SECTORAL SYNERGY: A LITERATURE REVIEW - Novianty Djafri; Al-Amin (CV. ADIBA AISHA AMIRA, 2025)
This research examines the impact of multisectoral synergy in improving education quality through a comprehensive literature review. This approach involves collaboration between the government, private sector and non-governmental organisations (NGOs) to pool and utilise diverse resources, expertise and technology to address educational challenges. The results of the study show that inter-sectoral synergies not only contribute to improving infrastructure and enhancing the quality of teaching staff, but also introduce more interactive and contextualised learning methods. These partnership programmes are able to create learning environments that are inclusive and adaptive to local needs, and enable equitable access to education to remote areas. In conclusion, sustained collaboration between sectors is essential to achieve a comprehensive improvement in the quality of education and provide a long-term positive impact on students' future readiness